Análise multifatorial de mecanismos patogenéticos implicados na infecção por Trypanosoma cruzi em camundongos BALB/c - Claudiney Melquiades Rodrigues (2010)
A century after the discovery of the Trypanosoma cruzi, many uncertainties remain with respect to factors determining the pathogenesis of Chagas disease. In the present work, the effects of the association of two T. cruzi populations with opposite virulence and pathogenicity in BALB/c mice were investigated through of the simultaneous analyses of multiple biological parameters during the acute phase of infection. For this, the animals were infected with 100 trypomastigotes of JG or CL Brener or coinfected with 50 trypomastigotes of each one of the respective T. cruzi populations by i.p. route. The systemic effects of the disease were assessed through analyses of the parasitemia, body weight and survival during the acute phase of infection. Alternatively, the animals were sacrificed at 7, 14 and 21 days post infection (p.i.) for simultaneous analyses of multiple biological parameters. JG single infected mice presented reduced parasitemia and heart parasitism, serum levels of pro-inflammatory mediators (TNF-, CCL2, IL-6 and IFN-) similar to those found among naïve animals, none clinical manifestations of toxemia and null mortality. On the other hand, CL Brener single infected mice presented higher parasitemia and heart parasitism, as well as an increased systemic release of pro-inflammatory mediators and higher mortality probably due to a toxic shock-like systemic inflammatory response. Interesting, coinfection with JG and CL Brener strains resulted in intermediate parasitemia, heart parasitism and mortality in relation to BALB/c mice single infected with JG or CL Brener. This was accompanied by a significant increase in the systemic release of IL-10, what suggest that the endogenous production of this important regulatory cytokine can be crucial for counterbalance the potentially lethal pathological effects triggered by concomitant release of pro-inflammatory mediators induced by CL Brener infection. In conclusion, our results suggest that the clonal complexity of the infecting T. cruzi population plays an important role in the host response to infection and clinical evolution of the disease in experimentally infected BALB/c mice. The combination of JG and CL Brener was able to induce both protective immunity and regulatory mechanisms that seemingly were sufficient to attenuate pathological damages caused by inflammation in BALB/c mice.